The legal basis of Sami reindeer herding rights in Sweden - Torp, Eivind (Mittuniversitetet, Avdelningen för ekonomivetenskap och juridik, 2013)
This article discusses the basis of the Sami right to pursue reindeer herding, and how that right has been regulated in law. Two aspects of this right are particularly significant: establishing which land areas are covered by the reindeer herding right and clarifying what that right entails. The legal institution of 'immemorial prescription' has long been considered highly significant in judicial trials concerning the reindeer herding rights. In the wake of a ruling by the Swedish Supreme Court, that picture has now changed.